Prioritization of critically unwell children in low resource primary healthcare centres in Cape Town, South Africa - Hansoti, Bhakti (Division of Emergency Medicine, 2017)
Background: Every day, sick children die from time sensitive preventable illnesses. Due to an inadequate number of trained healthcare workers and high volumes of children presenting to Primary Healthcare Centres (PHC), waiting times remain high and often result in significant delays for critically ill children. Delays in the recognition of critically unwell children are a key contributing factor to avoidable childhood mortality in Cape Town, South Africa. Methodology: A stepped implementation approach was undertaken to develop and evaluate a context-appropriate prioritization tool to identify and expedite the care of critically ill children PHC in Cape Town, South Africa. Aim 1: To conduct a systematic review of paediatric triage and prioritization tools for low resource settings in order to evaluate the evidence supporting the use of these tools. Aim 2: To perform an exploratory study, to identify barriers to optimal care for critically ill children in the pre-hospital setting in Cape Town, South Africa. Aim 3: To develop an implementable context-appropriate tool to identify and expedite the care of critically ill children in PHC in the City of Cape Town, South Africa. Aim 4: Evaluate the reliability of this tool compared to established triage tools currently used in this setting. Aim 5: Evaluate the impact of implementing this tool, on waiting times for children presenting for care to PHC. Aim 6: Evaluate the effectiveness of this tool post real-world implementation in identifying and expediting the care for critically ill children. Findings: Post real world implementation SCREEN was able to significantly reduce waiting times in PHC for critically ill children. Compared to pre-SCREEN implementation, post-SCREEN the proportion of critically ill children who saw a PN within 10 minutes increased tenfold from 6.4% (pre-SCREEN) to 64% (post-SCREEN) (p<0.001). SCREEN is also able to accurately identify critically ill children, in an audit of 827 patient-charts SCREEN had a sensitivity of 94.2% and a specificity of 88.1% when compared to IMCI. Interpretation: The SCREEN program when implemented in a real-world setting has shown that it can effectively identify and expedite the care of critically ill children in PHC.